Method for producing rare earth magnet powder
By performing hydrogen crushing and HDDR processing on the cast alloy, the problem of insufficient magnetic properties of rare earth magnet powder in the prior art is solved, and the manufacturing of rare earth magnet powder with high magnetic characteristics is realized, which is suitable for high-performance magnetic materials for bonding magnets.
Patent Information
- Application Number
- CN201980047246.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-19
- Filing Date
- 2019-07-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-07-17
AI Technical Summary
The prior art is difficult to effectively improve the magnetic characteristics of rare earth magnet powder through traditional hydrogen treatment methods, especially the manufacturing method of rare earth magnet powder suitable for bonded magnets is insufficient.
By hydrogen crushing the cast alloy pre-solution treatment, the obtained magnet raw materials are subjected to HDDR (including d-HDDR) to obtain rare earth magnet powder with high magnetic characteristics. During the hydrogen crushing process, it is exposed to a hydrogen atmosphere of 350℃ to 585℃, which promotes hydrogen to mainly invade the grain boundary phase without invading the main phase, thereby reducing intragranular cracks and improving magnetic characteristics.
The manufacturing of rare earth magnet powder with higher magnetic properties than traditional methods is achieved, and high-performance magnetic materials suitable for bonding magnets.
Smart Images

Figure CN112424888B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing rare earth magnet powder for use in bonded magnets and the like. Background Art
[0002] Bonded magnets obtained by consolidating rare earth magnet powders with a binder resin have excellent shape freedom and high magnetic properties, so they are often used in various electromagnetic devices such as electrical products and automobiles that are expected to save energy and reduce weight. In order to further expand the use of bonded magnets, it is hoped that the magnetic properties of rare earth magnet powders will be improved. Therefore, various schemes for hydrogen treatment in the manufacturing process of rare earth magnet powders have been proposed, and relevant records are found in the following patent documents.
[0003] It should be noted that hydrogen treatment mainly includes a disproportionation reaction using hydrogen absorption (Hydrogenation-Disproportionation / also referred to as "HD reaction") and a recombination reaction using dehydrogenation (Desorption-Recombination / also referred to as "DR reaction"). The HD reaction and the DR reaction are combined and referred to as "HDDR reaction", and the hydrogen treatment is referred to as "HDDR (treatment)". By the way, the HDDR mentioned in this specification also includes d-HDDR (dynamic-Hydrogenation-Disproportionation-Desorption-Recombination) as an improved type unless otherwise specified.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 3871219
[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-127648
[0008] Patent Document 3: Japanese Patent Application Publication No. 2008-305908 Summary of the invention
[0009] Problems to be solved by the invention
[0010] Patent document 1 describes the following topic: a magnet raw material having an average particle size of less than 10 mm is obtained by mechanically crushing an ingot by a jaw crusher, and the magnet raw material is subjected to d-HDDR having a low-temperature hydrogenation process (room temperature × 100 kPa), a high-temperature hydrogenation process, a structure stabilization process and a controlled exhaust process, thereby obtaining rare earth anisotropic magnet powder with high magnetic properties.
[0011] Patent Document 2 describes that rare earth anisotropic magnet powder with high magnetic properties can be obtained by subjecting a raw material alloy storing hydrogen (150° C.×250 kPa) to an HDDR process in which hydrogen gas is introduced after the temperature is raised to slow down the HD reaction.
[0012] It should be noted that the subject of hydrogen pulverizing a raw material alloy (about 300° C.×130 kPa) is described in Patent Document 3. However, Patent Document 3 is directed to sintered magnets, not bonded magnets.
[0013] The present invention has been made under such circumstances, and an object of the present invention is to provide a method for producing rare earth magnet powder having high magnetic properties suitable for bonded magnets by a method different from the conventional method.
[0014] Means for solving problems
[0015] The inventors have conducted in-depth research to solve this problem and have newly discovered that rare earth magnet powder with higher magnetic properties than before can be obtained by performing HDDR (including d-HDDR) on magnet raw materials obtained by hydrogen treatment (hydrogen crushing) of cast alloys under predetermined conditions. By further developing this result, the present invention described below was completed.
[0016] 《Method for producing rare earth magnet powder》
[0017] (1) The present invention is a method for manufacturing rare earth magnet powder, wherein the manufacturing method comprises: a disproportionation step, wherein a magnet raw material is caused to absorb hydrogen to undergo a disproportionation reaction, wherein the magnet raw material is obtained by exposing a cast alloy containing a rare earth element (referred to as "R"), boron (B) and a transition element (referred to as "TM") to a hydrogen atmosphere at 350°C to 585°C; and a recombination step, wherein hydrogen is desorbed from the magnet raw material after the disproportionation step to undergo a recombination reaction.
[0018] (2) According to the manufacturing method of the present invention, by exposing the cast magnet alloy (cast alloy) to a hydrogen atmosphere in a higher temperature range than before, a magnet raw material is subjected to HDDR, thereby obtaining a rare earth magnet powder with high magnetic properties. The reason for this is not clear, but the currently thought mechanism will be described later.
[0019] It should be noted that, in this specification, regardless of the state of the magnet raw material supplied to the HDDR (block, particle, powder, etc.), the treatment of exposing the cast alloy to a hydrogen atmosphere in order to obtain the magnet raw material is referred to as "hydrogen crushing". The cast alloy after hydrogen crushing is usually easy to break, and forms a coarse block or particle shape with a slight degree of crushing. The magnet raw material can be supplied to the HDDR as it is in a coarse state, or it can be further crushed into a fine state and then supplied to the HDDR.
[0020] 《Magnet raw materials, rare earth magnet powder, composites, bonded magnets》
[0021] The present invention can be understood as a magnet raw material obtained by hydrogen crushing (the magnet raw material in powder state is also referred to as "raw material powder"), and a magnet powder obtained by the above-mentioned manufacturing method. In addition, the present invention can also be understood as a bonded magnet comprising rare earth magnet powder and a resin that consolidates the powder particles. Furthermore, the present invention can also be understood as a composite for manufacturing the bonded magnet. The composite is a material obtained by pre-attaching a resin as a binder to the surface of each powder particle. It should be noted that the magnet powder used for the bonded magnet and the composite can also be a composite powder in which a plurality of magnet powders having different average particle sizes, alloy compositions, etc. are mixed.
[0022] "other"
[0023] (1) The rare earth magnet powder involved in the present invention can be an isotropic magnet powder, but an anisotropic magnet powder with higher magnetic properties is preferred. Anisotropic magnet powder contains magnet particles whose magnetic flux density (Br) in one direction (easy magnetization axis direction, c-axis direction) is greater than the magnetic flux density in other directions. Isotropy and anisotropy can be distinguished by the degree of anisotropy (DOT: Degree of Texture) = [Br( / / )-Br(⊥)] / Br( / / ) obtained when a magnetic field is applied parallel ( / / ) and perpendicular (⊥) to the c-axis direction. If the DOT value is 0, it is isotropic, and if it is greater than 0, it is anisotropic.
[0024] (2) "R" as used in this specification may be one or more of Y, lanthanide elements or actinide elements, and is mainly Nd. TM is one or more of 3d transition elements (Sc to Cu) or 4d transition elements (Y to Ag), and is any element of Groups 8 to 10 (especially Fe, Co, Ni), but is mainly Fe. It should be noted that part of B may be substituted by C.
[0025] The magnet raw material or magnet powder may contain modifying elements and (inevitable) impurities that are effective in improving the properties. Examples of modifying elements include Cu, Al, Ti, V, Cr, Ni, Zn, Ga, Zr, Nb, Mo, Sn, Hf, Ta, W, Dy, Tb, and Co that are effective in improving the coercive force.
[0026] (3) Unless otherwise specified, "x to y" in this specification includes a lower limit x and an upper limit y. Any numerical value included in the various numerical values or numerical ranges described in this specification can be used as a new lower limit or upper limit to set a new range such as "a to b". In addition, "x to y kPa" means xkPa to ykPa, and the same applies to other units. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] [ Figure 1A ] is a flow chart showing the manufacturing process of magnet powder.
[0028] [ Figure 1B ] is a diagram showing the hydrogen atmosphere during hydrogen crushing.
[0029] [ Figure 1C ] is a diagram showing other modes of hydrogen atmosphere during hydrogen crushing.
[0030] [ Figure 2 ] are SEM images obtained to observe the appearance of each magnet raw material (raw material block) obtained by hydrogen crushing under different conditions.
[0031] [ Figure 3A ] is a SEM image obtained by comparing the appearance and cross-section of magnet raw material particles obtained by hydrogen crushing at different atmosphere temperatures.
[0032] [ Figure 3B ] is a scatter diagram showing the relationship between the hydrogen fragmentation temperature and the average particle size of the raw material powder.
[0033] [ Figure 4A ] is a SEM image obtained by comparing the appearance and cross-section of each powder (magnet powder) obtained by implementing d-HDDR on each raw material powder obtained by hydrogen crushing at different atmosphere temperatures.
[0034] [ Figure 4B ] is a scatter diagram showing the relationship between the hydrogen crushing temperature of the raw material powder and the average particle size of the magnet powder.
[0035] [ Figure 5A ] is a scatter diagram showing the relationship between the hydrogen crushing temperature of the raw material powder and the maximum energy product of the magnet powder.
[0036] [ Figure 5B ] is a scatter diagram showing the relationship between the hydrogen crushing temperature of the raw material powder and the residual magnetic flux density of the magnet powder.
[0037] [ Figure 5C ] is a scatter diagram showing the relationship between the hydrogen crushing temperature of the raw material powder and the coercive force of the magnet powder.
[0038] [ Figure 6] is a scatter diagram showing the relationship between hydrogen fragmentation temperature and crack density.
[0039] [ Figure 7 ] is an explanatory diagram of the mechanism of crack generation in the main phase and grain boundary phase.
[0040] [ Fig. 8A ] is a scatter diagram showing the relationship between the dispersion treatment temperature of the ingot and the maximum energy product of the magnet powder.
[0041] [ Figure 8B ] is a scatter diagram showing the relationship between the dispersion treatment temperature of the ingot and the residual magnetic flux density of the magnet powder.
[0042] [ Figure 8C ] is a scatter diagram showing the relationship between the dispersion treatment temperature of the ingot and the coercive force of the magnet powder.
[0043] [ Fig.9A ] is a scatter diagram showing the maximum energy product of each magnet powder obtained by hydrogen crushing and then HDDR treatment.
[0044] [ Fig. 9B ] is a scatter diagram showing the residual magnetic flux density of each of these magnet powders.
[0045] [ Fig. 9C ] is a scatter diagram showing the coercive force of each of these magnet powders. DETAILED DESCRIPTION
[0046] One or more constituent elements arbitrarily selected from this specification may be added to the constituent elements of the present invention described above. The contents described in this specification not only appropriately correspond to the manufacturing method of the present invention, but also appropriately correspond to magnet raw materials, rare earth magnet powders, composites, bonded magnets, etc. Even constituent elements in the method may become constituent elements related to the object. Which embodiment is the best varies depending on the object, required performance, etc.
[0047] Magnet Raw Materials
[0048] (1) Casting alloy
[0049] The casting alloy may be an ingot alloy obtained by pouring a R-TM-B alloy melt into a mold and solidifying it, or may be a rapidly solidified alloy obtained by rapidly solidifying the melt. The rapidly solidified alloy may be obtained, for example, by a strip casting method.
[0050] The casting alloy preferably includes an ingot that has been solution treated (process) before hydrogen fracturing. Since the ingot alloy solidifies slowly (cooling rate is low), the soft magnetic αFe phase is easy to crystallize (remain). When the ingot alloy is solution treated, the αFe phase disappears, segregation, etc. are eliminated, and a homogeneous structure with fine grain growth (for example, grain size: 50μm to 250μm) is obtained.
[0051] Since the quenched solidified alloy solidifies faster (cooling rate is high) than the ingot alloy, the soft magnetic αFe phase hardly precipitates (remains) or only precipitates in a small amount. Therefore, the quenched solidified alloy has a relatively homogeneous crystal structure compared to the ingot alloy. When the quenched solidified alloy is subjected to solution treatment, it becomes a structure mainly composed of fine grain growth (for example, grain size: 50μm to 250μm).
[0052] The purpose of solution treatment is not necessarily the same in ingot alloys and quenched solidified alloys. However, for any alloy, the metal structure of the cast alloy before hydrogen cracking is made into a desired form by solution treatment. It should be noted that solution treatment can also be appropriately referred to as homogenization heat treatment.
[0053] The solution treatment can be performed by heating the cast alloy before hydrogen cracking at 1050° C. to 1250° C., or further at 1100° C. to 1200° C. in a treatment furnace (heating furnace). The treatment time can be, for example, 3 hours to 50 hours, or further at 10 hours to 40 hours. The treatment atmosphere can be an inert atmosphere (an inert gas atmosphere such as Ar or a vacuum atmosphere).
[0054] It is also possible to perform a heat treatment (called "R-rich dispersion treatment") in which the cast alloy (ingot) after the solution treatment is heated in a temperature range lower than the treatment temperature of the solution treatment and higher than the treatment temperature (hydrogen crushing temperature) of the hydrogen crushing described later. The treatment temperature can be, for example, 650°C to 900°C, 650°C to 800°C, and further 680°C to 750°C. The treatment time can be, for example, 10 minutes to 10 hours, and further 0.5 hours to 3 hours. The treatment atmosphere can be, for example, an inert atmosphere (an inert gas (Ar, etc.) atmosphere or a vacuum atmosphere, etc.). The R-rich dispersion treatment promotes the dispersion (distribution) of the rare earth element (R) to the grain boundaries of the cast alloy, and each grain of the cast alloy becomes uniformly covered with an R-rich phase. It is believed that when such a cast alloy is subjected to hydrogen crushing treatment, fracture (separation) at the grain boundaries of the cast alloy occurs more preferentially, and it is easy to obtain a magnet raw material with fewer intragranular cracks.
[0055] (2) Alloy composition
[0056] Composition of R2TM 14The theoretical composition of the tetragonal compound of the B1-type crystal (main phase) is R: 11.8 atomic %, B: 5.9 atomic %, TM: balance in terms of atomic % (at %). When the casting alloy is richer in R than its theoretical composition value, it is preferred because it can achieve the optimization of the particle size distribution after hydrogen crushing and the high coercivity of the rare earth magnet powder. Therefore, when the entire casting alloy is set to 100 atomic %, it is preferred that the R of the casting alloy is 11 atomic % to 15 atomic %, and further 12 atomic % to 13 atomic %, and B is 5 atomic % to 9 atomic %, and further 6.2 atomic % to 7 atomic %.
[0057] (3) Hydrogen crushing (process)
[0058] The magnet raw material is obtained by subjecting the above-mentioned cast alloy to a specific hydrogen treatment (raw material hydrogen treatment). The treatment (hydrogen crushing and then hydrogen pulverization) is carried out by exposing the cast alloy placed in a treatment furnace to a hydrogen atmosphere of 350°C to 585°C, 400°C to 575°C, and then 425°C to 550°C (hydrogen absorption process). The atmosphere temperature is the temperature at which the cast alloy is kept at a substantially constant temperature. As long as the atmosphere temperature is within a predetermined range, the hydrogen partial pressure can be low or high. Of course, in order to consider the efficiency and safety during hydrogen crushing, the hydrogen partial pressure is preferably 1kPa to 250kPa, and then 5kPa to 150kPa.
[0059] Hydrogen fracturing is performed, for example, by evacuating a treatment furnace containing a casting alloy and then introducing hydrogen into the treatment furnace. The gas introduced into the treatment furnace may be hydrogen alone or may be introduced together with an inert gas. The latter is preferred from the perspective of easier control of the hydrogen partial pressure. In addition, the gas introduced into the treatment furnace may be in a flowing state. Hydrogen fracturing may be performed, for example, for 0.5 to 10 hours, and further for 1 to 5 hours, after the atmosphere temperature reaches the target temperature. It is preferred that hydrogen be introduced into the furnace after the atmosphere temperature (or the temperature of the casting alloy) reaches a predetermined value.
[0060] The cast alloy exposed to the hydrogen atmosphere absorbs hydrogen to the extent that it self-collapses or slightly breaks to obtain a block with a maximum length of about several cm to about several mm. Such a magnet raw material is called a "raw material block". The raw material block obtained after hydrogen crushing can be crushed separately and then pulverized, so that the magnet raw material made into a powder (raw material powder) with a particle size (maximum diameter) of about 100μm to about 1mm is supplied to the next process (HDDR). It should be noted that the magnet raw material supplied to the HDDR can be in a state of absorbing hydrogen or in a state of dehydrogenated magnet raw material. By the way, it is difficult to strictly distinguish between "crushing" and "pulverization", but if it is necessary to distinguish, the case where shear force is applied to intentionally refine the particles is "pulverization", and the case where a slight impact is applied to break the block is "crushing".
[0061] In the case of discontinuously performing the manufacture of magnet raw materials (hydrogen crushing process) and the manufacture of magnet powder (HDDR process), the magnet raw materials that have released the absorbed hydrogen can be supplied to the HDDR. By inserting the hydrogen release process, the degradation of the magnet raw materials before the HDDR can be prevented. The hydrogen release process can be released at the same temperature (350°C to 585°C) as when hydrogen is absorbed, and then cooled to near room temperature (RT).
[0062] (4) Supply form to HDDR
[0063] The main purpose of the hydrogen crushing of the present invention is not to crush and granulate the casting alloy itself. The purpose of the present invention is to minimize the generation of cracks in the individual grains (single crystal grains) constituting the casting alloy. When the casting alloy is exposed to a high-temperature hydrogen atmosphere as in the hydrogen crushing of the present invention, hydrogen hardly invades the grains, but mainly invades the grain boundary phase (R-rich phase / Nd-rich phase) existing between the grains (grain boundaries). As a result, cracks caused by the volume expansion of the grain boundary phase accompanying hydrogen invasion occur preferentially at the grain boundaries. In this way, it can be considered that the casting alloy after hydrogen crushing has obtained a magnet raw material containing grains with almost no cracks. In this way, as a result of supplying a magnet raw material containing grains with few cracks to the HDDR, it is inferred that a magnet powder with high magnetic properties is obtained. It should be noted that the casting alloy (magnet raw material) after hydrogen crushing may be particles (single crystal grains) containing the above-mentioned grain monomers, or may contain aggregates of the grains (polycrystalline grains). The raw material block described above usually contains polycrystalline grains.
[0064] Therefore, as described above, the magnet raw material obtained by hydrogen crushing the cast alloy can be directly supplied to the HDDR without special pulverization (for example, keeping the raw material in a lump state). That is, the cast alloy (magnet raw material) after hydrogen crushing does not necessarily have to be in a powder state.
[0065] Of course, the magnet raw material (raw material powder) that has been slightly crushed, pulverized, classified, and adjusted in particle size can also be supplied to the HDDR in consideration of the specifications of the magnet powder, the manufacturing process (equipment), and the specifications of the bonded magnet. The particle size adjustment can, for example, make the average particle size 30 μm to 200 μm. The average particle size is greatly affected by the grain diameter of the casting structure before hydrogen crushing, but the magnet raw material after hydrogen crushing can also be further crushed to adjust to the desired average particle size.
[0066] The average particle size (also referred to as "average powder particle size") referred to in this specification is defined as follows. First, a powder of -212 μm is taken as the object by crushing or sieving. The powder is sieved (classified) into 0 (μm) to 53 (μm), 53 (μm) to 75 (μm), 75 (μm) to 106 (μm), 106 (μm) to 150 (μm) and 150 (μm) to 212 (μm). The weight ratio (called "weight frequency") of each classified powder (y to x: μm) relative to the whole is calculated. For each classified powder, the product of the average particle size ((y+x) / 2: μm) and the weight frequency is calculated. The total of the products is referred to as the "average particle size" (average powder particle size).
[0067] It should be noted that the expressions according to the sieving method (reference: JIS Z 8801) have the following meanings: -xμm: powder passing through a sieve with a mesh size of x (μm) (powder with a maximum particle size of less than xμm), (+)yμm: powder not passing through a sieve with a mesh size of y (μm) (powder with a minimum particle size of more than yμm), y(μm) to x(μm): powder passing through a sieve with a mesh size of x (μm) and not passing through a sieve with a mesh size of y (μm).
[0068] Incidentally, particle size measurement using a laser diffraction method was not performed because the magnet raw material after hydrogen crushing was further atomized by the high-pressure gas injected before the measurement, making it impossible to perform appropriate measurement.
[0069] Magnetic Powder
[0070] The magnet raw material (raw material powder / raw material block) after hydrogen crushing is subjected to hydrogen treatment (HDDR) to obtain magnet powder, wherein the magnet powder contains fine R2TM 14 A polycrystal (magnetic particle) composed of an aggregate of B1 type crystals (average crystal grain diameter: 0.05 μm to 1 μm).
[0071] (1) When HDDR is roughly divided, it includes a disproportionation process (HD) and a recombination process (DR). The disproportionation process is a process of exposing the magnet raw material placed in the treatment furnace to a predetermined hydrogen atmosphere to cause the magnet raw material after hydrogen absorption to undergo a disproportionation reaction. The disproportionation process can be carried out, for example, at a hydrogen partial pressure of 10 kPa to 300 kPa, an atmosphere temperature of 600°C to 900°C, and a treatment time of 1 hour to 5 hours.
[0072] The recombination step is a step of dehydrogenating the magnet raw material after the disproportionation step to cause the magnet raw material to undergo a recombination reaction. The recombination step can be performed, for example, at a hydrogen partial pressure of 1 kPa or less, an atmosphere temperature of 600°C to 900°C, and a treatment time of 1 to 5 hours.
[0073] (2) All or part of the HD step or the DR step can be performed as the following steps.
[0074] (a) Low temperature hydrogenation process
[0075] The low-temperature hydrogenation process is a process in which the magnet raw material in the treatment furnace is kept in a hydrogen atmosphere below the temperature at which the disproportionation reaction occurs (for example, room temperature to 300°C, and further room temperature to 100°C). Through this process, the magnet raw material is in a state of pre-absorbing hydrogen, and the disproportionation reaction caused by the subsequent high-temperature hydrogenation process (equivalent to the disproportionation process) proceeds slowly. As a result, it becomes easy to control the reaction rate of the positive structural phase transition. The hydrogen partial pressure at this time can be, for example, about 30 kPa to about 100 kPa. It should be noted that, as mentioned above, the hydrogen atmosphere referred to in this specification may also be a mixed gas atmosphere of hydrogen and an inert gas (the same below).
[0076] (b) High temperature hydrogenation process
[0077] The high-temperature hydrogenation process is a process of keeping the magnet raw material after the low-temperature hydrogenation process in a hydrogen atmosphere with a hydrogen partial pressure of 10kPa to 60kPa and 750°C to 860°C. Through this process, the magnet raw material after the low-temperature hydrogenation process undergoes a disproportionation reaction (positive phase change reaction) to form a three-phase decomposition structure (αFe phase, RH2 phase, Fe2B phase).
[0078] It should be noted that in this process, the hydrogen partial pressure or the atmosphere temperature may not always be constant. For example, at the end of the process where the reaction rate is reduced, at least one of the hydrogen partial pressure or the temperature may be increased to adjust the reaction rate and promote three-phase decomposition (structure stabilization process).
[0079] (c) Controlled exhaust process
[0080] The controlled exhaust process is a process of maintaining the magnet raw material after the high-temperature hydrogenation process in a hydrogen atmosphere with a hydrogen partial pressure of 0.7kPa to 6kPa and a temperature of 750℃ to 850℃. Through this process, the magnet raw material after the high-temperature hydrogenation process undergoes a recombination reaction (reverse phase change reaction) accompanied by dehydrogenation. As a result, the three-phase decomposition structure becomes a fine R2TM obtained by removing hydrogen from the RH2 phase and transferring the crystal orientation of the Fe2B phase. 14 B1 type crystalline hydride (RFeBH X ). The recombination reaction in this step proceeds slowly because it is carried out under a relatively high hydrogen partial pressure. It should be noted that if the high-temperature hydrogenation step and the controlled exhaust step are carried out at approximately the same temperature, it is easy to transition from the high-temperature hydrogenation step to the controlled exhaust step by simply changing the hydrogen partial pressure.
[0081] (d) Forced exhaust process
[0082] The forced exhaust step can be performed, for example, at 750° C. to 850° C. in a vacuum atmosphere of 1 Pa or less. This step removes hydrogen remaining in the magnet raw material, thereby completing dehydrogenation.
[0083] It should be noted that the forced exhaust process and the controlled exhaust process do not need to be performed continuously. A cooling process for cooling the magnet raw material can be performed after the controlled exhaust process, and the forced exhaust process can be performed in batches. In order to suppress the growth of grains, the cooling after the forced exhaust process is preferably quenching.
[0084] (3) Diffusion treatment can be performed to increase the coercive force. Diffusion treatment can be performed, for example, by heating a mixed raw material obtained by mixing the magnet raw material with the diffusion raw material. 14 A non-magnetic phase is formed on the surface or grain boundary of the B1 type crystal, thereby improving the coercive force of the magnet particles. The diffusion treatment is carried out, for example, by heating the powder obtained by mixing the diffusion raw material powder with the magnet powder obtained after the HDDR in a vacuum atmosphere or an inert gas atmosphere. When the magnet raw material and the diffusion raw material are pre-mixed in any one of the low-temperature hydrogenation process, the high-temperature hydrogenation process, the controlled exhaust process or the forced exhaust process, the subsequent process also serves as the diffusion treatment. The diffusion raw material is, for example, a heavy rare earth element (Dy, Tb, etc.), an alloy or compound thereof (such as fluoride), an alloy of a light rare earth element (such as Cu alloy, Cu-Al alloy) or a compound.
[0085] (4) Magnetic powder
[0086] The magnet powder obtained after HDDR (including d-HDDR) (rare earth magnet powder after the recombination step) has an average particle size of, for example, 30 μm to 200 μm, (larger than) 50 μm to 190 μm, and further 55 μm to 180 μm.
[0087] "use"
[0088] The rare earth magnet powder of the present invention can be used in many ways, a representative example of which is a bonded magnet. The bonded magnet mainly comprises rare earth magnet powder and a binder resin. The binder resin can be a thermosetting resin or a thermoplastic resin. In addition, the bonded magnet can be a bonded magnet obtained by compression molding or a bonded magnet obtained by injection molding. When a bonded magnet using rare earth anisotropic magnet powder is formed in an oriented magnetic field, it can exhibit high magnetic properties.
[0089] Example
[0090] like Figure 1AAs shown, the ingot (cast alloy) after the solid solution treatment is subjected to various hydrogen crushings with different hydrogen atmospheres. The magnet raw materials after the hydrogen crushing are lightly crushed and then classified by screening. The raw material powders thus obtained are subjected to HDDR treatment to obtain magnet powders. Then, the magnetic properties of each magnet powder are evaluated. The present invention is described in detail below based on such embodiments.
[0091] 《Sample Manufacturing》
[0092] [Example 1]
[0093] (1) Casting alloy
[0094] Raw materials weighed to have a desired alloy composition (Nd: 12.5 atomic%, B: 6.4 atomic%, Nb: 0.2 atomic%, Ga: 0.3 atomic%, Fe: balance) were melted in a high-frequency melting furnace to obtain an ingot (cast alloy).
[0095] (2) Solution treatment
[0096] The ingot was heated at 1140° C. for 20 hours in an Ar gas atmosphere to be homogenized.
[0097] (3) Hydrogen crushing
[0098] The ingot after solution treatment was subjected to hydrogen crushing as follows. First, the treatment furnace containing the ingot was evacuated (10 -2 Pa or less). Then, the vacuumized furnace is heated. Figure 1B As shown, it takes 1 hour to make the desired atmosphere temperature in the treatment furnace. Then, hydrogen is introduced into the treatment furnace to reach the desired hydrogen partial pressure. This state is maintained for 5 hours (hydrogen absorption process). At this time, the hydrogen partial pressure is 10 kPa or 100 kPa, and the atmosphere temperature is any temperature between room temperature (RT) and 600°C. It should be noted that the atmosphere temperature in the treatment furnace is measured by a thermocouple in contact with each ingot, and the hydrogen partial pressure is measured by a pressure gauge set in the treatment furnace.
[0099] Then, the furnace is cooled to room temperature while maintaining the hydrogen partial pressure. The hydrogen in the treatment furnace is replaced with an inert gas (Ar at atmospheric pressure), and the magnet raw material after hydrogen crushing treatment is taken out from the furnace in the Ar atmosphere. Slight crushing is applied to the magnet raw material whose atmosphere temperature is set to RT~500℃. The magnet raw material whose atmosphere temperature is set to 550℃ or 600℃ is difficult to powderize only by slight crushing, so mechanical crushing is applied. The obtained powders are classified by sieve to obtain a raw material powder of -212μm. The crushing and classification at this time are carried out in an inert gas atmosphere.
[0100] By the way, hydrogen fragmentation can also be used Figure 1C The mode shown is performed in place of Figure 1B The mode shown. Figure 1C In this mode, after the hydrogen absorption step, the furnace is cooled to room temperature 0.5 hours (30 minutes) after the hydrogen in the treatment furnace is exhausted. Figure 1B The same pattern is used. Figure 1C The magnet raw materials after processing in the mode of Figure 1B The magnet raw materials processed in the same mode can obtain magnet powder with the same characteristics.
[0101] (4) HDDR processing
[0102] The processing furnace containing each raw material powder (15 g) obtained by hydrogen crushing at different temperatures was evacuated. The hydrogen partial pressure and temperature in the processing furnace were controlled to perform HDDR treatment on each raw material powder. Specifically, each raw material powder was subjected to a disproportionation reaction (positive phase change reaction) by a high-temperature hydrogenation process (820°C × 30 kPa × 3 hours) (disproportionation process).
[0103] Next, a controlled exhaust step (820°C × 5 ~ 1 kPa × 1.5 hours) of continuously exhausting hydrogen from the processing furnace and a subsequent forced exhaust step (820°C × 10 -2 Pa×0.5 hours). In this way, each raw material powder undergoes a recombination reaction (reverse phase change reaction) (recombination process). Then, Ar gas is introduced to quench the processed material in the processing furnace (cooling process). The processed material is gently crushed in Ar gas and then classified (sieved) to obtain a magnet powder with a particle size of -212μm.
[0104] "observe"
[0105] (1) Magnet raw materials after hydrogen crushing
[0106] The morphologies of the magnet raw materials (raw material blocks) obtained by hydrogen crushing the ingots under various conditions were observed using a scanning electron microscope (SEM). Figure 2 Compare and show in.
[0107] The raw material block after hydrogen crushing treatment was set to room temperature (RT) × 100 kPa or 500°C × 100 kPa in the hydrogen atmosphere of the treatment furnace, and the particles of the obtained raw material powder were observed using SEM. Its appearance and cross section are shown in Figure 3A .
[0108] (2) Magnet powder after HDDR
[0109] The same HDDR conditions were applied to raw material powders with different hydrogen crushing atmosphere temperatures (hydrogen crushing temperatures), and the particles of each magnet powder obtained were observed using SEM. The appearance and cross section are shown in FIG. Figure 4A .
[0110] Determination
[0111] (1) Average particle size
[0112] The average particle size of each raw material powder obtained by hydrogen crushing and then pulverizing under different atmospheres is shown in FIG. Figure 3B In addition, the average particle size of the magnet powder obtained by subjecting each raw material powder to HDDR under the same conditions is also shown. Figure 4B The average particle size was measured for each powder after classification (-212 μm). The average particle size was calculated by the method described above.
[0113] (2)Magnetic properties
[0114] The magnetic properties of each magnet powder obtained by subjecting each raw material powder with different hydrogen crushing treatment conditions to the same HDDR conditions are measured as follows. Each magnet powder is placed in a capsule, oriented in a magnetic field (1193 kA / m) in molten paraffin (about 80°C), and then magnetized (3580 kA / m). The magnetic properties of the magnetized magnet powder are measured using a vibrating sample magnetometer (VSM). At this time, the density of each magnet powder is assumed to be 7.5 g / cm 3 The maximum energy product (BH) of each magnet powder thus obtained is max ), residual flux density (Br) and coercive force (Hc) are shown in Figure 5A , Figure 5B and Figure 5C (They are combined and referred to as "Figure 5").
[0115] "evaluate"
[0116] (1) Magnet raw materials
[0117] Depend on Figure 2 It is clear that when hydrogen crushing is performed in a hydrogen atmosphere in the room temperature range as in the conventional method, many cracks of different sizes are generated in both the grain boundary phase and the main phase.
[0118] On the other hand, as the atmosphere temperature at which hydrogen breaks down (called hydrogen break down temperature (T HD)) increases, and cracks decrease. It was also found that this tendency is almost unaffected by the hydrogen partial pressure and mainly depends on the hydrogen crushing temperature. However, it is believed that when the atmosphere temperature during hydrogen crushing reaches 600°C, a partial disproportionation reaction (HD reaction) and melting of the R-rich phase (Nd-rich phase) occur.
[0119] When the hydrogen crushing temperature reaches 400℃~500℃, the number of fine cracks is significantly reduced, and the cracks are mainly generated in the grain boundary phase and are almost invisible in the main phase. Figure 3A This tendency is also clearly seen in the SEM image shown. Figure 3B The average particle size is shown.
[0120] (2) Magnetic powder
[0121] When the general Figure 3A and Figure 3B (The two figures are combined and referred to as "Figure 3") and Figure 4A and Figure 4B (The two figures are combined and referred to as "Figure 4" for short) It is clear that the particle morphology after HDDR roughly reflects the particle morphology after hydrogen crushing. It is clear from Figure 5 that the magnetic properties of the magnet powder (involved in Example 1) increase with the hydrogen crushing temperature, and Br or (BH) max The peak value is shown when the hydrogen fragmentation temperature is 450℃ to 500℃. If we focus on (BH) as a comprehensive magnetic property index, max , it is clear that the hydrogen fragmentation temperature can be set to 350° C. to 585° C., 400° C. to 575° C., and further to 425° C. to 550° C. It should be noted that the anisotropy (DOT) of the magnet powder according to Example 1 is 0.69 to 0.73.
[0122] Investigation
[0123] As described above, it is known that by performing HDDR using a magnet raw material (raw material powder) obtained by hydrogen crushing in a specific temperature range, a magnet powder having higher magnetic properties than before can be obtained. Although the reason for this is not necessarily clear, it is currently considered as follows.
[0124] (1) Crack density
[0125] In order to study the above reasons, the density of cracks in each raw material block obtained by hydrogen crushing the ingot after the solution treatment in different atmospheres was determined. The crack density is an indicator of whether the crystal grains after hydrogen crushing are easy to break within the grains (in the main phase).
[0126] The crack density is calculated as follows. Each raw material block is observed using a field emission scanning electron microscope (FE-SEM). The SEM image is processed using image analysis software to calculate the total length of cracks in the grains (main phase) within a specific field of view (referred to as "intragranular crack length"). The total is divided by the specific field of view area to obtain the crack density. The results obtained in this way are shown in Figure 6 It should be noted that the grain boundary is based on rupture and this part is not included in the calculation of crack length.
[0127] Depend on Figure 6 It is clear that the crack density decreases monotonically with the increase of hydrogen fragmentation temperature. It should be noted that when the hydrogen fragmentation temperature reaches 600°C, due to the HD reaction (hydrogenation disproportionation reaction), not only intragranular cracks but also grain boundary cracks are not observed.
[0128] (2) Mechanism
[0129] according to Figure 2 , Figure 3A , Figure 4A and Figure 6 The mechanism by which the manufacturing method of the present invention can produce magnet powder with higher magnetic properties than before is considered to be as follows. Figure 7 The gist of this is schematically shown in FIG.
[0130] First, if Figure 7 As shown in FIG. 1 , the cast alloy (ingot) after the solution treatment is composed of a main phase and a grain boundary phase surrounding the main phase. In the case where the cast alloy is a representative Nd-Fe-B magnet alloy, the main phase is Nd2Fe 14 B phase, the grain boundary phase is a Nd-rich phase (R-rich phase).
[0131] When the hydrogen crushing temperature is low as in the past, in the cast alloy (magnet raw material / raw material block) after hydrogen crushing, hydrogen invades not only the grain boundary phase but also the main phase, thereby generating cracks. When the raw material block is crushed (including crushing), magnet raw material particles are formed that break along any cracks inside and outside the main phase. Figure 3A As shown in the upper photograph, this morphology can be seen from the fact that each particle has a plurality of protrusions formed by brittle fracture within the particle.
[0132] Such magnet raw material particles have different easy magnetization axis directions ( Figure 7 The state in which multiple crystal grains (main phase) (arrows in the figure) are mixed. This state is also inherited by the magnet particles after HDDR. It is believed that as a result, even if HDDR is performed on the magnet raw material obtained by hydrogen crushing at low temperature, magnet powder with high magnetic properties (especially Br) cannot be obtained.
[0133] On the other hand, as in the present invention, when the hydrogen crushing temperature is high, in the cast alloy (raw material block) after hydrogen crushing, hydrogen mainly intrudes only into the grain boundary phase, and hydrogen hardly intrudes into the main phase, and cracks are mainly generated in the grain boundary phase. When the raw material block is crushed, magnet raw material particles are formed that are broken along the grain boundary phase during casting. Figure 3A This pattern can also be seen in the photo shown below.
[0134] Such magnet raw material particles are mainly composed of a single crystal grain (main phase) and are in a state where the easy magnetization axis direction is consistent. This state is also inherited by the magnet particles after HDDR. It is believed that as a result, when the magnet raw material obtained by hydrogen crushing at high temperature is subjected to HDDR, high magnetic properties (especially Br / Figure 5B ) of magnetic powder.
[0135] In addition, when HDDR is performed on magnet raw material particles having intragranular cracks as in the conventional art, the grain boundary phase (Nd-rich phase / R-rich phase: Figure 7 The grain boundary phase (not shown) on the surface of the magnet raw material particles (the thick white line portion at the lower right) melts and penetrates into the intragranular cracks ( Figure 7 The thick white single dotted line portion at the far right bottom) forms a pool phase (Nd-rich phase / R-rich phase). Accordingly, it is difficult to form a sufficient grain boundary phase (Nd-rich phase / R-rich phase: Figure 7 In this way, even if HDDR is performed on the magnet raw material obtained by hydrogen crushing at low temperature, high magnetic properties (especially Hc / Figure 5C ) of magnetic powder.
[0136] On the other hand, when HDDR is performed on magnet raw material particles with almost no intragranular cracks as in the present invention, the Nd-rich phase / R-rich phase is not wastefully aggregated, and sufficient grain boundary phases (Nd-rich phase / R-rich phase: Figure 7 It is believed that when the magnet raw material obtained by hydrogen crushing at high temperature is subjected to HDDR, high magnetic properties (especially Hc / Figure 5C ) of magnetic powder.
[0137] By the way, compare Figure 5A , Figure 5B and Figure 6 It is clear that the Br or BHmax of the magnet powder shows a decreasing trend in the hydrogen fracture temperature range (550°C to 600°C) after reaching the peak, although the crack density decreases. The reason is considered to be as follows.
[0138] As described above, the ingot (magnet raw material) obtained by hydrogen treatment at 550°C or 600°C is not powderized to a slight degree of crushing, but is mechanically crushed to obtain raw material powder of a predetermined particle size before being supplied to the HDDR. Figure 2 As can be seen from the photographs shown, the reason why such pulverization treatment is considered necessary is that, when hydrogen treatment is performed at 550° C. or 600° C., there are almost no cracks not only in the grains but also in the grain boundaries, and the steel is in a state that is not easily broken.
[0139] By applying a relatively larger pulverizing force during the pulverization process than during the crushing process, cracks penetrating through the grains are generated in the hydrogen-treated ingot. As a result, in the raw material powder supplied to the HDDR, polycrystalline grains (see Figure 7 ) increases again. It is considered that due to this influence, the Br or BHmax of the magnet powder obtained from the magnet raw material whose hydrogen fragmentation temperature is set to 550°C or 600°C is lower than the peak value.
[0140] [Example 2]
[0141] (1) The ingot subjected to R-rich dispersion treatment after solution treatment (before hydrogen dispersion treatment) was subjected to hydrogen dispersion treatment and HDDR treatment. The treatment was performed in the same manner as in Example 1 except for the R-rich dispersion treatment. The R-rich dispersion treatment was performed as follows.
[0142] The treatment furnace containing the solution treated ingot is evacuated (10 -2 The vacuumed treatment furnace was heated to a pressure of 10 Pa or less in the treatment furnace (hydrogen partial pressure: 10 -2 The atmosphere temperature of the molten metal was changed to any temperature between 500°C and 900°C. This state was maintained for 1 hour (R-rich dispersion treatment step). Next, the process was changed to a hydrogen fragmentation treatment atmosphere (500°C×100 kPa) for a predetermined time.
[0143] (2) The treatment temperature of the R-rich dispersion treatment (referred to as "dispersion treatment temperature (Tr)") and the magnetic properties (BH) of each magnet powder obtained were compared. max The relationship between Br and Hc is shown in Figure 8A to Figure 8C (These are collectively referred to as "FIG. 8" for short.) The magnetic properties were measured by the method described above. It should be noted that "untreated" shown in FIG. 8 represents a magnet powder obtained by hydrogen crushing (500°C x 100 kPa) of an ingot that has not been subjected to R-rich dispersion treatment (equivalent to the magnet powder of Example 1).
[0144] As is clear from FIG8 , the magnetic properties are further improved by performing the R-rich dispersion treatment. In particular, when the dispersion treatment temperature is set to be higher than 600°C or 650°C, (BH) maxOr Br is significantly increased. This tendency does not change even when the dispersion treatment temperature is set to 900°C. However, when the dispersion treatment temperature exceeds 750°C, Hc tends to decrease. When a magnet powder with high coercive force is required, the dispersion treatment temperature can be below 750°C, and further below 720°C. It should be noted that the anisotropy (DOT) of the magnet powder obtained by setting the dispersion treatment temperature to 700°C is 0.76.
[0145] [Example 3]
[0146] (1) Magnet raw materials were not taken out from the treatment furnace after hydrogen crushing, and HDDR treatment was continued after hydrogen crushing (hydrogen partial pressure: 100 kPa, atmosphere temperature: 500°C, maintained for 5 hours), and magnet powders (Sample 31, Sample 32) were also obtained. At this time, vacuuming before HDDR treatment performed in Example 1 was not performed. In addition, mechanical crushing and classification were not performed after hydrogen crushing, but after HDDR treatment. Other than this, the treatment was carried out in the same manner as in Example 1.
[0147] Sample 31 is a magnet powder obtained by subjecting a magnet raw material to HDDR treatment after hydrogen crushing while maintaining a hydrogen partial pressure (100 kPa) and then cooling the furnace to room temperature. Sample 32 is a magnet powder obtained by subjecting the magnet raw material to HDDR treatment without subjecting the furnace to hydrogen crushing and subjecting the magnet raw material to atmosphere adjustment. It should be noted that a magnet powder (Sample C) was also produced by changing the atmosphere temperature of the hydrogen crushing performed in Sample 31 to room temperature (23°C).
[0148] (2) The magnetic properties (BH) of the magnet powder of each sample were max , Br, Hc) are shown in Figures 9A to 9C (These are collectively referred to as "FIG. 9"). The magnetic properties were measured by the methods described above. The dotted line in FIG. 9 represents the magnetic properties of the magnet powder equivalent to Example 1 obtained by hydrogen crushing under the same conditions (500°C x 100 kPa).
[0149] As is clear from FIG. 9 , even when the HDDR treatment is continued after hydrogen fragmentation, high magnetic properties (especially Br, (BH)) can be obtained as in Example 1. max ) of the magnet powder. It should be noted that the anisotropy (DOT) of the magnet powder involved in Samples 31 and 32 was 0.71 to 0.74.
Claims
1. A method for producing rare earth magnet powder, wherein: The manufacturing method has the following features: a disproportionation step in which a magnet raw material is made to absorb hydrogen to undergo a disproportionation reaction, the magnet raw material being obtained by setting the atmosphere temperature in a treatment furnace containing a casting alloy to 350° C. to 585° C. and then introducing a hydrogen atmosphere into the treatment furnace to expose the casting alloy to the hydrogen atmosphere, wherein the casting alloy contains a rare earth element, boron and a transition element; and a recombination step, in which hydrogen is removed from the magnet raw material after the disproportionation step to cause a recombination reaction; The casting alloy includes an ingot subjected to a solution treatment, and the ingot subjected to the solution treatment is heat treated at a temperature lower than the treatment temperature of the solution treatment and within a temperature range of 650° C. to 900° C.
2. The method for producing rare earth magnet powder according to claim 1, wherein: The hydrogen partial pressure of the hydrogen atmosphere is 1 kPa to 250 kPa.
3. The method for producing rare earth magnet powder according to claim 1 or 2, wherein: When the entire casting alloy is assumed to be 100 atomic %, the rare earth element of the casting alloy is 11 atomic % to 15 atomic % and the boron is 5 atomic % to 9 atomic %.
Citation Information
Patent Citations
Method for producing rare earth anisotropic magnet powder
JP2008127648A
METHOD FOR MANUFACTURING R-Fe-B PERMANENT MAGNET
JP2008305908A
R-Fe-B microcrystalline high-density magnet and process for production thereof
CN101379574A
Rare-earth anisotropic magnet powder, method for producing same, and bonded magnet
CN102648502A
Rare earth-iron-boron magnet powder and process of producing same
CN1033018A